A decade of nitrous oxide (N2O) monitoring in full-scale wastewater treatment processes: A critical review. (15th September 2019) - Vasilaki, V.; Massara, T.M.; Stanchev, P.; Fatone, F.; Katsou, E.
Abstract: Direct nitrous oxide (N2 O) emissions during the biological nitrogen removal (BNR) processes can significantly increase the carbon footprint of wastewater treatment plant (WWTP) operations. Recent onsite measurement of N2 O emissions at WWTPs have been used as an alternative to the controversial theoretical methods for the N2 O calculation. The full-scale N2 O monitoring campaigns help to expand our knowledge on the N2 O production pathways and the triggering operational conditions of processes. The accurate N2 O monitoring could help to find better process control solutions to mitigate N2 O emissions of wastewater treatment systems. However, quantifying the emissions and understanding the long-term behaviour of N2 O fluxes in WWTPs remains challenging and costly. A review of the recent full-scale N2 O monitoring campaigns is conducted. The analysis covers the quantification and mitigation of emissions for different process groups, focusing on techniques that have been applied for the identification of dominant N2 O pathways and triggering operational conditions, techniques using operational data and N2 O data to identify mitigation measures and mechanistic modelling. The analysis of various studies showed that there are still difficulties in the comparison of N2 O emissions and the development of emission factor (EF) databases; the N2 O fluxes reported in literature vary significantly even among groups of similar processes. The results indicated that the duration of the monitoring campaigns can impact the EF range. Most N2 O monitoring campaigns lasting less than one month, have reported N2 O EFs less than 0.3% of the N-load, whereas studies lasting over a year have a median EF equal to 1.7% of the N-load. The findings of the current study indicate that complex feature extraction and multivariate data mining methods can efficiently convert wastewater operational and N2 O data into information, determine complex relationships within the available datasets and boost the long-term understanding of the N2 O fluxes behaviour. The acquisition of reliable full-scale N2 O monitoring data is significant for the calibration and validation of the mechanistic models -describing the N2 O emission generation in WWTPs. They can be combined with the multivariate tools to further enhance the interpretation of the complicated full-scale N2 O emission patterns. Finally, a gap between the identification of effective N2 O mitigation strategies and their actual implementation within the monitoring and control of WWTPs has been identified. This study concludes that there is a further need for i) long-term N2 O monitoring studies, ii) development of data-driven methodological approaches for the analysis of WWTP operational and N2 O data, and iii) better understanding of the trade-offs among N2 O emissions, energy consumption and system performance to support the optimization of the WWTPs operation. Graphical abstract: Image 1 Highlights: N2 O emissions benchmarking in wastewater is hindered by non-standard reporting. Structured methodological approaches for N2O data analysis are still missing. Mechanistic models must be calibrated with long-term full-scale data. Isotopic analyses should be coupled with mechanistic/data-driven models. Studies validating N2 O mitigation measures are still missing.